2014
DOI: 10.1111/gfl.12086
|View full text |Cite
|
Sign up to set email alerts
|

Origins of formation waters in the Llanos foreland basin of Colombia: geochemical variation and fluid flow history

Abstract: Wells located in the Colombian Andean foreland often produce biodegraded hydrocarbons and relatively fresh water (total dissolved solids concentrations of 2000 mg l−1 dominate across most of the basin). The ratio of water to hydrocarbon in the produced fluids is high and has often been interpreted by explorationists and simulation engineers as being due to massive meteoric water invasion. To challenge this hypothesis, previously published and existing data are compiled here, along with 68 new water samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The same Californian sequence also shows a whole-rock δD enrichment that would correspond to a decrease in the water δD consistent with our measurements, although obscured by a strong scatter. Gonzalez-Penagos et al 36 also observed an increase of pore water δ 18 O with depth in the Colombian shales they studied undergoing S/I conversion.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The same Californian sequence also shows a whole-rock δD enrichment that would correspond to a decrease in the water δD consistent with our measurements, although obscured by a strong scatter. Gonzalez-Penagos et al 36 also observed an increase of pore water δ 18 O with depth in the Colombian shales they studied undergoing S/I conversion.…”
Section: Resultsmentioning
confidence: 84%
“…There, very low TDS water was present and initially attributed to an influx of meteoric water but later determined to be S/I conversion. Gonzalez-Penagos et al relied on water isotopes (relatively heavier δ 18 O) and basic geochemistry (increase in dissolved silica) to show that what was believed to be massive topographically driven (Andes) meteoric water invasion in a deep onshore basin in Colombia was better explained by additional water release from S/I conversion. Studies in offshore Japan showed water freshening at a depth of 1 km (and temperature of 100 °C) in a Miocene-to-recent volcano-clastic sequence. , …”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been argued that basal reservoirs in the Llanos basin are underpressured with flow back into the basin . It has also been argued that the Llanos basin was a tight, low-permeability system with very little fluid flow (and thus no water washing) . However, the explanation in reference is consistent with a substantial tilt to the OWC in the Rubiales reservoir.…”
Section: Introductionmentioning
confidence: 94%
“…Consequently, rivers draining this relief have metamorphic rocks in their riverbeds and lower values of electric conductivity and lower concentrations of ions, such as in Guiana Shield streams. Raised ridges, on the other hand, shaped strong lateral influences that have driven the distribution of salinity concentrations at the basin lowlands (Gonzalez‐Penagos et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Stream water pH captures the geochemical signal of waters flowing through a basin, and its variability reflects the cumulated effect of past historical events. In the Orinoco basin, pH values vary with the geological age of ecoregions (Gonzalez-Penagos et al, 2014;Goosen, 1971;Stallard, 1985). Consequently, lower pH values usually occur in the oldest ecoregions as they have experienced the highest number of weathering cycles (e.g., Guiana shield, Goosen, 1971).…”
Section: Historical Imprints On Taxon Distribution: the Significancmentioning
confidence: 99%